2021
DOI: 10.1253/circj.cj-21-0023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hemodynamic Outcomes in 121 Patients Who Underwent Perceval Sutureless Aortic Valve Implantation ― Early Results From a Single Korean Institution ―

Abstract: arious new technical approaches have emerged as promising alternatives to conventional aortic valve replacement (AVR) for severe aortic stenosis in the elderly and high-risk patients with multiple comorbidities. Transcatheter aortic valve implantation (TAVI) and rapid deployment or sutureless AVR (SU-AVR) are among the most promising approaches.Several studies on SU-AVR reported that this method could reduce the time of aortic cross-clamp (ACC) and cardiopulmonary bypass (CPB). Moreover, SU-AVR facilitates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[40][41][42][43] Surgical implantation technique may also contribute to atrioventricular conduction disorders. 41,[44][45][46] Accurate annulus decalcification, positioning of guide suture, minimizing the traction on the valve commissures, and the balloon pressure may reduce the rate of pacemaker implantation after sutureless AVR. 44,47) Though the present meta-analysis indicated that the rate of pacemaker implantation was higher following Perceval implantation, at study level, high heterogeneity can be evidenced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] Surgical implantation technique may also contribute to atrioventricular conduction disorders. 41,[44][45][46] Accurate annulus decalcification, positioning of guide suture, minimizing the traction on the valve commissures, and the balloon pressure may reduce the rate of pacemaker implantation after sutureless AVR. 44,47) Though the present meta-analysis indicated that the rate of pacemaker implantation was higher following Perceval implantation, at study level, high heterogeneity can be evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…41,[44][45][46] Accurate annulus decalcification, positioning of guide suture, minimizing the traction on the valve commissures, and the balloon pressure may reduce the rate of pacemaker implantation after sutureless AVR. 44,47) Though the present meta-analysis indicated that the rate of pacemaker implantation was higher following Perceval implantation, at study level, high heterogeneity can be evidenced. Indeed, there are several studies that found similarity in the rate of peacemaker implantation 7,11) and some other that reported even a lower rate in favor of the Perceval valve.…”
Section: Discussionmentioning
confidence: 99%
“…11 Compared with their Western counterparts, elderly Japanese patients tend to have a smaller body and reduced aortic annular diameter. 12 Although a few studies have presented findings of early outcomes and thrombocytopenia in relation to Perceval SU-AVR procedures conducted by institutions in Asia, 13 the results of a large cohort treated in Japan have yet to be published. The present study was conducted to assess postoperative thrombocytopenia and early clinical outcomes in 121 patients with severe AS who underwent a Perceval SU-AVR procedure via a conventional median sternotomy or mini-sternotomy at a single Japanese institution.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no complications due to thrombocytopenia, Perceval indications should be reconsidered, such as for patients who require antiplatelet medication, have a history of gastrointestinal bleeding, and/or are prone to falling. Conversely, use of a Perceval prosthesis provides the possibility of better AVR with shortened CPB and ACC times, extremely rare in patients with a complete atrioventricular block and PVL, as well as Hospital stay (days) 12 [10][11][12][13][14][15] Ventilation duration (hours) 8 [6][7][8][9][10][11][12] Blood transfusion (intra-or postoperative) 75 (62. The present analysis revealed 3 independent predictors of severe thrombocytopenia: advanced age (>80 years), the use of a median sternotomy approach, and a preoperative low platelet count (<200×10 3 /µL).…”
Section: Discussionmentioning
confidence: 99%
“…A premarketing study has been started in China recently (PERCEVAL S Valve Clinical Study for Chinese Registration [PERFECT] NCT03481387). The largest available published cohort is from Korea, with 121 patients (mean age 74.7 ± 6.2 years, 53.7% women) implanted between 2014 and 2019 [ 21 ]. In this Korean cohort, Perceval valve implantation provided a significant cardiac-related survival benefit with good early hemodynamic and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%